Students' Perceptions of Using Online Mind Mapping in Academic Essay Writing Instruction - Dwi Atmoko; Fiqih Kartika Murti; Agung Tyas Subekti (Indonesian Language Education and Literature, 2026)
This study aimed to describe students' perceptions of using online mind mapping as a pre-writing strategy in academic essay writing instruction. The research used a quantitative approach with a descriptive survey design. The research subjects were 48 students from the Bachelor of Nursing Science Study Program at Universitas Bhamada Slawi who were taking the Indonesian Language course and had used the online mind mapping application (Coggle) in academic essay writing instruction. Sampling was done purposively, considering the students' experience in using online mind mapping. The research instrument was a four-point likert scale questionnaire developed based on the constructs of technology perception and writing instruction. The questionnaire indicators included ease of use, idea development and organisation, essay structure composition, material understanding, writing motivation, quality of written results, efficiency of the writing process, and satisfaction with using online mind mapping. The collected data was analysed using descriptive statistics, calculating mean values, percentages, and standard deviations to objectively describe the trends in student perceptions. The research results indicated that students had a positive perception of using online mind mapping as a pre-writing strategy. The average questionnaire score fell within the range of 3.27–3.63, indicating an agreement to strongly agree category. Online mind mapping is perceived as making it easier for students to develop and organise ideas, structure essays more systematically, improve understanding of essay writing material, and boost motivation and efficiency in the writing process. Additionally, students also showed a high level of satisfaction and interest in continuing to use online mind mapping in writing instruction. The implications of this research suggest that online mind mapping has the potential to be sustainably integrated as a pre-writing strategy in academic essay writing instruction at the university level. This finding can serve as the basis for developing technology-based writing instruction, as well as encourage further research with experimental designs to objectively test its impact on writing quality. Persepsi Mahasiswa terhadap Penggunaan Mind Mapping Online dalam Pembelajaran Menulis Esai Akademik Penelitian ini bertujuan untuk mendeskripsikan persepsi mahasiswa tentang penggunaan mind mapping online sebagai strategi pra-penulisan dalam pengajaran penulisan esai akademik. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei deskriptif. Subjek penelitian adalah 48 mahasiswa dari Program Studi Sarjana Keperawatan di Universitas Bhamada Slawi yang mengambil mata kuliah Bahasa Indonesia dan telah menggunakan aplikasi mind mapping online (Coggle) dalam pengajaran penulisan esai akademik. Pengambilan sampel dilakukan secara purposif, dengan mempertimbangkan pengalaman mahasiswa dalam menggunakan mind mapping online. Instrumen penelitian berupa kuesioner skala likert empat poin yang dikembangkan berdasarkan konstruk persepsi teknologi dan pengajaran penulisan. Indikator kuesioner meliputi kemudahan penggunaan, pengembangan dan pengorganisasian ide, komposisi struktur esai, pemahaman materi, motivasi menulis, kualitas hasil tulisan, efisiensi proses penulisan, dan kepuasan menggunakan mind mapping online. Data yang dikumpulkan dianalisis menggunakan statistik deskriptif, menghitung nilai rata-rata, persentase, dan deviasi standar untuk secara objektif menggambarkan tren persepsi mahasiswa. Hasil penelitian menunjukkan bahwa mahasiswa memiliki persepsi positif terhadap penggunaan peta pikiran daring sebagai strategi pra-penulisan. Skor kuesioner rata-rata berada dalam kisaran 3,27–3,63, menunjukkan kategori setuju hingga sangat setuju. Peta pikiran daring dianggap memudahkan mahasiswa untuk mengembangkan dan mengatur ide, menyusun esai secara lebih sistematis, meningkatkan pemahaman materi penulisan esai, dan meningkatkan motivasi serta efisiensi dalam proses penulisan. Selain itu, mahasiswa juga menunjukkan tingkat kepuasan dan minat yang tinggi untuk terus menggunakan peta pikiran daring dalam pengajaran penulisan. Implikasi penelitian ini menunjukkan bahwa peta pikiran daring berpotensi untuk diintegrasikan secara berkelanjutan sebagai strategi pra-penulisan dalam pengajaran penulisan esai akademik di tingkat universitas. Temuan ini dapat menjadi dasar untuk mengembangkan pengajaran penulisan berbasis teknologi, serta mendorong penelitian lebih lanjut dengan desain eksperimental untuk secara objektif menguji dampaknya terhadap kualitas penulisan.